Follow the rain? Environmental drivers of Tyrannus migration across the New World - MacPherson, Maggie P.; Jahn, Alex E. [UNESP]; Murphy, Michael T.; Kim, Daniel H.; Cueto, Victor R.; Tuero, Diego T.; Hill, Elliot D. (Oxford Univ Press Inc, 2018)
Predictable seasonal changes in resources are thought to drive the timing of annual animal migrations; however, we currently understand little about which environmental cues or resources are tracked by different migratory bird species across the planet. Understanding which environmental cues or resources birds track in multiple migratory systems is a prerequisite to developing generalizable conservation plans for migratory birds in a changing global environment. Within the New World, climatic differences experienced by Nearctic-Neotropical migratory (NNM; i.e. breed in North America and spend the nonbreeding period in the Neotropics) and Neotropical austral migratory (NAM; i.e. breed and spend the nonbreeding period wholly within South America) bird species suggest that their migratory strategies may be shaped by unique selective pressures. We used data gathered from individuals fitted with light-level geolocators to build species distribution models (SDMs) to test which environmental factors drive the migratory strategies of species in each system. To do so, we evaluated whether temperature, precipitation, and primary productivity (NDVI) were related to the seasonal distributions of an NNM (Eastern Kingbird [Tyrannus tyrannus]) and NAM species (Fork-tailed Flycatcher [T. savana]). Both Eastern Kingbird and Fork-tailed Flycatcher locations were positively correlated with high precipitation during their nonbreeding seasons. Eastern Kingbird locations were positively correlated with both NDVI and temperature during their breeding season and both pre-and post-breeding migrations. Fork-tailed Flycatcher locations were positively correlated with both temperature and precipitation during both migrations, but only temperature during the breeding season. The value of extending the application of geolocator data, such as in SDMs, is underscored by the finding that precipitation was such an important predictor of the nonbreeding distributions of both types of migrants, as it remains unclear how global climate change will affect wet-dry cycles in the tropics.
Keywords: migration; seasonality; species distribution model; geolocator; climate; Maxent